Innovative Approaches to Teaching Foreign Languages at the University - Shchebunyaeva, Natalia Germanovna (2021)
The article is concerned with the substantiation of innovative approaches to teaching foreign languages at the university. It is established that during the professional training of specialists at the university, the special emphasis should be given to the application of innovative forms and methods of training aimed at qualitative mastering of knowledge, abilities, and skills, developing students’ mental activities, identifying skills of critical addressing the problems, gaining experience of independent learning of training materials, conducting exploration work, and gaining qualities that will be useful in professional activities and later in life. It is proved that the effectiveness of teaching foreign languages at the university will depend on the desire and ability of teachers to take advantage of successful practices in the humanistic approach to teaching, understanding the need to abandon authoritarian and scholastic teaching methods.